Numerical Simulation on Characteristics of Heat Transfer with Different Elliptic Tube Cross Sections. (September 2020) - Gao, Quanfu; Ma, Sen
Abstract: With the developing of manufacturing technique and the lack of material in recent years, the elliptic tube-fin bank heat exchangers have been paid more and more attentions. The numerical simulation has become an important mean and effective way for studying the flow and heat transfer. The heat transfer capacity of the heat exchanger is affected by multiple factors, among which the cross sections of the elliptic tube is a major factor. In this article, we take numerical analysis methods and SIMPLE algorithm in body-fitted coordinate system to analyze the effect of the different elliptic cross sections on heat transfer characteristics, the results will provide basis for designing and manufacturing compact heat exchangers.